2020
DOI: 10.1007/s10900-020-00933-6
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study in Academic-Community Partnerships: A Community-Based Nutrition Education Program for Mexican Immigrants

Abstract: Hispanics are the largest U.S. immigrant group and Mexican Americans are the largest U.S. Hispanic population. Hispanics, particularly Mexican Americans, are among the highest risk groups for obesity, placing them at increased risk for cardiovascular disease and certain types of cancer. Obesity lifestyle interventions incorporating Motivational Interviewing techniques and specific adaptations for the population of interest can have a significant impact on reducing health risks. This paper presents a community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Academic-community partnerships are well established as a cost-effective approach for addressing nutrition challenges and public health disparities (43)(44)(45)(46) . A large body of research involving academic-community partnerships has reported significant valuable benefits such as shared resources, building institutional capacity, additional funding, managing and enhancing new ideas, providing real-world learning opportunities for students' skills and opportunities to extend and conduct new areas of research (47,48) . This approach allows for an exchange of ideas and expertise shared between universities and community members across all stages of the programme, from design, implementation and dissemination (48) .…”
Section: Discussionmentioning
confidence: 99%
“…Academic-community partnerships are well established as a cost-effective approach for addressing nutrition challenges and public health disparities (43)(44)(45)(46) . A large body of research involving academic-community partnerships has reported significant valuable benefits such as shared resources, building institutional capacity, additional funding, managing and enhancing new ideas, providing real-world learning opportunities for students' skills and opportunities to extend and conduct new areas of research (47,48) . This approach allows for an exchange of ideas and expertise shared between universities and community members across all stages of the programme, from design, implementation and dissemination (48) .…”
Section: Discussionmentioning
confidence: 99%
“…To date, steps in the EBQI process have included (1) the formation of local teams to consider data on barriers and facilitators to implementation and (2) drafting, iterating, and planning a locally contextualized implementation strategy to increase uptake of an EBI ( 20 ). Additionally, EBQI activities have been described as: stakeholder planning meetings using expert panel techniques to identify priorities, formative evaluation, development and training of local QI champion and team members, practice facilitation, and review of local QI proposals ( 5 ); monthly calls to facilitate collaboration and spread of EBIs; and technical work groups to support local priorities for EBIs ( 23 ). A recent scoping review of EBQI found the most common components across 211 studies to be: use of research to select effective interventions, engagement of stakeholders (i.e., partners), iterative development, partnering with frontline implementers, and data driven evaluation ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of engaging community partners in all aspects of research is grounded in the notion that the population impacted by the issue, condition, or situation has a unique perspective on the resolution of the issue, which is critical to ensuring the effectiveness and adequacy of health interventions in broader community settings (2,3). Engaging community partners in health research has been proven to be significant in efforts to improve population health in areas such as diabetes, nutrition, infant mortality, cancer, obesity, dental hygiene, etc (4)(5)(6)(7)(8). Dissemination and implementation (D&I) science researchers began to describe the need for participatory engagement among local practitioners nearly two decades ago (9).…”
Section: Introductionmentioning
confidence: 99%